Radiologically revealed spine osteoporosis in male with hypertension and coronary heart disease - P A Chizhov; Y I Ivanova; Y N Pribytkov; N N Beloselsky (Научно-практическая ревматология)
Radiologically revealed spine osteoporosis in male with hypertension and coronary heart disease Objective. To study prevalence and intensity of spine osteoporosis (OP) in men suffering from hypertension (H) and coronary heart disease (CHD). Material and methods. 101 men with H and CHD aged 50 to 78 years (mean age 60,6±0,85 years) and 37 men of control group without cardiovascular diseases aged 50-66 years (mean age 58,6±0,74 years) were examined. Clinical examination, radiological, radiomorphometric spine examination and echocardioscopy were performed. Results. OP was revealed in 34,65% of main group pts what is 3,2 times more frequent than in control group (10,8%, p<0,05). OP intensity in men with H and CHD was significantly higher than in healthy people. Vfertebral fractures were revealed in 12,87+3,3% of main group pts and only in 2,7±2,7% in control group (p<0,05). OP development dependence from cardiac history duration and cardiac pathology severity was demonstrated. Conclusion. The results of the study show significantly higher prevalence of spine OP among men suffering from H and CHD. Long history and severity of cardiovascular pathology clinical signs promote OP frequency and severity increase.